1985
DOI: 10.1172/jci111812
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic properties in rabbits of heparin and heparin fragments covalently coupled to human antithrombin III.

Abstract: Clinical grade heparin is a very heterogeneous mucopolysaccharide, containing molecules with M, ranging from 6,000 to 30,000 that have either a high affinity or a low affinity for antithrombin III (AT). In this study, the antithrombotic properties of intact high-affinity heparin (M, = 15,000) and of two heparin fragments (h16, a 16-monosaccharide fragment, with M, = 4,300, and h12, a 12-monosaccharide fragment, with M, = 3,200) and of their functional covalent stoichiometric complexes with human AT were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Doutremepuich and his coworkers, 12 ' 13 comparing heparin fractions of 25,000, 18,000, 16,000, 8000, 7000, 5000, and 2000 daltons in a ligated vena cava model (rat), found that only the 25,000 heparin failed to limit the extension of the preformed thrombus. Mattsson et al 34 noticed that when they covalently coupled AT III to low molecular weight heparins (4300), the complex produced an antithrombotic effect three to four times longer than low molecular weight heparins alone.…”
Section: Platelet and Vesselmentioning
confidence: 99%
“…Doutremepuich and his coworkers, 12 ' 13 comparing heparin fractions of 25,000, 18,000, 16,000, 8000, 7000, 5000, and 2000 daltons in a ligated vena cava model (rat), found that only the 25,000 heparin failed to limit the extension of the preformed thrombus. Mattsson et al 34 noticed that when they covalently coupled AT III to low molecular weight heparins (4300), the complex produced an antithrombotic effect three to four times longer than low molecular weight heparins alone.…”
Section: Platelet and Vesselmentioning
confidence: 99%